Staphylococcus aureus and Pseudomonas aeruginosa infectious keratitis: key bacterial mechanisms that mediate pathogenesis and emerging therapeutics - Shah, Shalini; Wozniak, Rachel A. F. (Frontiers in Cellular and Infection Microbiology, 2023)
Bacterial keratitis (bacterial infection of the cornea) is a major cause of vision loss worldwide. Given the rapid and aggressive nature of the disease, immediate broad-spectrum antibiotics are essential to adequately treat this disease. However, rising antibiotic resistance continues to accelerate, rendering many commonly used therapeutics increasingly ineffective. As such, there is a significant effort to understand the basic pathogenesis of common causative organisms implicated in keratitis in part, to fuel the development of novel therapies to treat this blinding disease. This review explores two common causes of bacterial keratitis, Staphylococcus aureus and Pseudomonas aeruginosa, with regards to the bacterial mediators of virulence as well as novel therapies on the horizon.